A Peptide‐Conjugated Probe with Cleavage‐Induced Morphological Change for Treatment on Tumor Cell Membrane. Issue 11 (15th February 2023) - Zhang, Wei; Hu, Jing‐Jing; Liu, Rui; Dai, Jun; Yuan, Lizhen; Liu, Yiheng; Chen, Bochao; Gong, Mingxing; Xia, Fan; Lou, Xiaoding
Abstract: Despite the promising advancements of in situ forming nanoassembly for the inhibition of tumor growth and metastasis, the lack of sufficient triggering sites and hardly controlling the forming position restrict their further developments. Herein, a smart transformable peptide‐conjugated probe (DMFA) with enzyme cleavage‐induced morphological change is designed for treatment on the tumor cell membrane. Specifically, after self‐assembling into nanoparticles and anchoring on the cell membrane with sufficient interaction sites rapidly and stably, DMFA will be efficiently cleaved into α ‐helix forming part (DP) and β ‐sheet forming part (LFA) by overexpressed matrix metalloproteinase‐2. Thus, the promoted Ca 2+ influx by DP‐induced cell membrane breakage and decreased Na + /K + ‐ATPase activity by LFA‐assembled nanofibers wrapping the cells can inhibit PI3K‐Akt signaling pathway, leading to the inhibition of tumor cell growth and metastasis. This peptide‐conjugated probe undergoes in situ morphological transformation on the cell membrane, exhibiting great potential in tumor therapy. Abstract : To achieve the effective inhibition of tumor growth and metastasis, a smart transformable peptide‐conjugated probe DMFA with matrix metalloproteinase‐2 cleavage‐induced morphological change is designed. By ensuring the sufficient interaction sites between the α ‐helix and phospholipid bilayer and the precise formation of β ‐sheet‐based nanofibers outside the cell membrane, tumor growth and metastasis could be efficiently prevented by this treatment method.